2020
DOI: 10.3390/foods9040416
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography Mass Spectrometry Quantification of α-solanine, α-chaconine, and Solanidine in Potato Protein Isolates

Abstract: For potato proteins to be used as a food ingredient, the level of natural potato defense substances, the glycoalkaloids (GAs), should be limited. In this work, a method is developed for quantification of the two major potato GAs, α-solanine and α-chaconine, as well as for their aglycon form, solanidine, using liquid chromatography–mass spectrometry single quadrupole in single ion monitoring mode. Standard solutions of GA and a food-grade potato protein powder was used to validate the method. A linear correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Glycoalkaloids were extracted from the samples as previously described with modifications. Briefly, 10 μL of samples was added with 990 μL of 5% acetic acid with 0.3 μg/mL tomatine (internal standard).…”
Section: Methodsmentioning
confidence: 99%
“…Glycoalkaloids were extracted from the samples as previously described with modifications. Briefly, 10 μL of samples was added with 990 μL of 5% acetic acid with 0.3 μg/mL tomatine (internal standard).…”
Section: Methodsmentioning
confidence: 99%
“…Tocosh comes from a fermentation process (Andean technique), which is suitable for distribution and consumption in the different markets of Peru as flour or in its raw form. On the other hand, the amount of glycoalkaloids are related to the cultivation method, storage and temperature, depending overall on the Andean techniques destined for its production and can be distributed in different rates in Solanum tuberosum tubers, they have been found in the tuber (smaller quantity), leaves and peel (greater quantity), and some analysis showed quantities such as 300-600 mg/kg in peel, 2000-4000 mg/kg in buds, and 3000-5000 mg/kg in flowers [20]. In our work, we did not evaluate the identification of constituents in tocosh flour by chromatography, but based on several studies of Solanum tuberosum, its glycoalkaloids are known by its fingerprint (α-solanine, α-chaconine and solanidine).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a study reported the development of an LC-ESI-MS method for the quantification of α-solanine, its aglycon form solanidine, and the α-chaconine in potato protein isolates [ 146 ]. After an extraction with acetic acid aqueous solution, sample extracts were purified by HLB Oasis cartridges.…”
Section: Glycoalkaloidsmentioning
confidence: 99%